Competition law : Competition law : current problems of criminal and non-criminal enforcement problems of criminal and non-criminal enforcement - Šošić, Miha (LeXonomica, 2021)
Infringements of competition law can be sanctioned as administrative or criminal offences. Such enforcement of competition law is connected with numerous problems, since not only the rationale of competition law has to be taken into account but also the fundamental principles of criminal law which are limiting the state’s power against individuals (natural or legal persons). Special emphasis has to be given to the principle of legality and procedural principles of a fair trial. The author comes to the conclusion that numerous problems regarding the substantive and procedural aspect of criminal enforcement of competition law in Slovenia remain unsolved. Konkurenčno kazensko in prekrškovno pravo : nekateri izbrani problem. Pri prekrškovnem in kazenskem sankcioniranju konkurenčnopravnih kršitev se odpirajo številni problemi, saj je poleg konkurenčnopravnih izhodišč potrebno upoštevati tudi posebnosti kaznovalnega prava, zlasti garancije, ki so potrebne za varstvo fizičnih in pravnih oseb pred zlorabo državne oblasti. Osrednjo vlogo pri tem imajo načelo zakonitosti in procesna jamstva, katerih namen je zagotavljanje poštenega prekrškovnega in kazenskega postopka. Avtor ugotavlja, da pri slovenski ureditvi konkurenčnega prekrškovnega in kazenskega prava številni problemi ostajajo odprti, tako z vidika materialnopravnih kot postopkovnih rešitev.